2022
DOI: 10.1111/jocd.15203
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous adverse events following 771 doses of the inactivated and mRNA COVID‐19 vaccines: A survey study among health care providers

Abstract: Introduction As Coronavirus disease 19 (COVID‐19) still continues to affect humanity worldwide, different types of COVID‐19 vaccines are being administered to maintain immunization against COVID‐19. As both the inactivated and mRNA vaccines are now being applied prevalently, systemic adverse events along with cutaneous side effects are frequently being reported in the literature. Aim In our study, we aimed to determine the cutaneous adverse effects of the inactivated (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…8 In this study, 130 participants (39.5%) reported discomfort at the injection site, the highest prevalence of AEFI symptoms in the first 15 minutes after immunization. Then, 44 individuals (16.9%) and 70Additionally, soreness at the injection site is the most prevalent adverse event connected to the site of injection, which is similar with previous research by Bostan et al, in which a local injection site response was the most often observed side effect 9. In this study, the perceived severity of AEFI was dominated by mild severity, while moderate, severe, and potentially life-threatening events occurred in a few cases only.…”
supporting
confidence: 85%
“…8 In this study, 130 participants (39.5%) reported discomfort at the injection site, the highest prevalence of AEFI symptoms in the first 15 minutes after immunization. Then, 44 individuals (16.9%) and 70Additionally, soreness at the injection site is the most prevalent adverse event connected to the site of injection, which is similar with previous research by Bostan et al, in which a local injection site response was the most often observed side effect 9. In this study, the perceived severity of AEFI was dominated by mild severity, while moderate, severe, and potentially life-threatening events occurred in a few cases only.…”
supporting
confidence: 85%
“…26 When compared with the Pfizer vaccine, CoronaVac was associated with a significantly lower incidence of local injection-site reactions. 27,28 There is a lack of knowledge about the cutaneous or systemic adverse effects of CoronaVac since the findings of the phase 3 trials have not been published yet.…”
Section: Early Unspecific Injection-site Reactionsmentioning
confidence: 99%
“…However, some patients received glucocorticoids, pain relievers, or antihistamines. 19,27,35,36,38,39 Moreover, many patients were given unneeded antibiotics due to fears of cellulitis or other infections, which emphasize the importance of improving the awareness of the physicians that there is no need to postpone the second dose of the vaccine due to the benign DLRs. Regarding the AstraZeneca vaccine, there are only very few scattered case reports documenting the presence of DLRs following the vaccine.…”
Section: Type IV (Delayed) Large Local Reactionsmentioning
confidence: 99%
“…We would like to share ideas on “Cutaneous Adverse Events Following 771 Doses of the Inactivated and mRNA COVID‐19 Vaccines: a Survey Study Among Health Care Providers 1 1 although no serious systemic or cutaneous adverse effects were detected in the study population. Although the COVID‐19 vaccine is good, we are all concerned that it may be detrimental as well.…”
mentioning
confidence: 99%